A simple calculation method to classify and individualize sports training: Ranking and classification - Merino-Muñoz, P.; Pérez-Contreras, J.; Balladares, H.; AedoMuñoz, E.; Cerda-Kohler, H. (Sport Performance & Science Reports, 2021)
Coaches must be familiar with analyzing their athletes' data sets for multiple reasons, such as monitoring, predicting performance, and individualizing training; the latter has become crucial in recent times. This note will present a method for ranking the athletes' data set and classifying them into smaller groups.